Analisis Faktor-Faktor yang Berpengaruh terhadap Perubaha Pola Menstruasi Akseptor KB Sunting Depo Medroksi Progresteraon Asetat (DMPA) di Wilayah Kerja Puskesmas Sokaraja I Purwokerto - Anggraeni, Mekar Dwi; Hartati, (Jurnal Keperawatan Soedirman, 2009)
Depo Medroksi Progesteron Asetat (DMPA) is an injection hormonal contraseption that has high efectiveness for family planing program. In the number of probability failure, it has approximately 0.25% of fail. However, DMPA has some side effect of disturbance menstruation pattern such as increasing body weight, headache and irregularity of hart rate (dysrytmia). The purpose of this research is to analyze factors (age, psychological stress, overload activity and accompanying disease) that influence of disturbance menstruation pattern of DMPA acceptor in Puskesmas Sokaraja I Purwokerto. This study used descriptive survey. The sample consists of 107 acceptor selected by proportional sampling. Data were collected using questionnaire. Chi Square and logistic regression method were used to analyze the data. The result shows that all factors such as age, psychological stress, high physical activity and history of accompanying disease have no significant influence towards disturbance menstruation pattern with chi square test at p=0.99, p = 0.98 p=0.91and p=0.93 respectively. There are no significant factors (age, psychological stress, high physical activity and history of accompanying disease) contribute to menstrual pattern for women who are using DMPA as part of family panning method